STYLISTIC OF THE QUR’AN: READING THE STORY OF SULAIMAN - Muhammad Afif Amrulloh; Munirul Ikhwan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
This paper examines the stylistic of Sulaiman's story in the Qur’an and its chronology. The language style has a building in the historical social context of the Arab community when it came down to the Qur’an. This article aimed to find the chronology and function of each language style used in the story of Sulaiman. This study was a library research with descriptive and analytical data presentation methods. The primary data were taken from the Qur’an in Surah Şād (30–40). A hetorical and chronological analysis wass used in this research. The finding of this study showed that the rhetoric of Sulaiman's story in Surah Şād still used a high style of language. Based on these findings, a strong language style is a characteristic of the Sulaiman's story to strengthen the prophet's heart, console the prophet and give the encouragement of spreading da’wa of Muhammad. This study contributes to a complete understanding of language style.